Pendugaan Komponen Ragam dan Nilai Heritabilitas pada Dua Populasi Cabai Rawit Merah (Capsicum frutescens L.) - Hakim, Abdul; Syukur, Muhamad; Wahyu, Yudiwanti (Jurnal Hortikultura Indonesia, 2019)
Assembling plant variety requires genetic information about the concerned traits. One way to obtain genetic information is through estimating genetic component and heritability. This experiment aims to obtain information varians component variety and heritability in 2 populations of bird pepper. Each population P1, P2, and F1 was planted with 40 plants, BCP1 and BCP 2 was planted with 100 plants and F2 was planted with 300 plants. Results in IPB C285 x IPB C290 population show the heritability broad sense with height category for all characters except fruit diameter. The number fruits per plant and fruit thickness has the highest category for heritability narrow sense. Results in IPB C321 x IPB C290 population heretability broad sense with hight category for all characters except weight per fruit. Fruit length was included in the high category for narrow sense heritability. The ratio of additive varians was greater than non additive varians in IPB C285 x IPB C290 population for number fruit per plant, weight per fruit, fruit length, fruit diameter, fruit thickness and harvest time while in IPB C321 x IPB C290 population number fruit per plant, fruit length, fruit thickness and fruit diameter. The selection method that can be used in both populations was the pedigree method so that selection activities can be carried out in early generation. The population IPB C285 x IPB C290 pedigree selection method was carried out on number fruits per plant and weight per fruit whereas in IPB C321 x IPB C290 population, pedigree selection method was carried out on fruit length. Keywords: additive, bird pepper, character, diversity, genetic, heritability